Increased Occurrence of Functional Movement Disorders during the COVID-19 Pandemic - K. P. Divya; Ajith Cherian; Naveen K. Paramasivan; S. Krishna; R. Amod; Soumya Sundaram (Annals of Movement Disorders)
BACKGROUND: An increase in functional movement disorders (FMDs) was perceived during the pandemic and an objective assessment of the same was performed. OBJECTIVE: To assess the frequency of FMDs during the coronavirus disease 2019 (COVID-19) pandemic compared to the pre-pandemic period and to identify the factors causing its increased incidence. METHODS: This cross-sectional comparison study conducted during the COVID-19 pandemic included patients attending the neurology outpatient department at a tertiary care center over a 6-month period. Those with FMDs documented by video evidence were compared against a baseline in the pre-pandemic period. Demographics, clinical features, duration of FMDs, presence of psychiatric comorbidity, as well as anxiety [by the Hospital Anxiety and Depression Scale (HADS-A)], depressive symptoms (HADS-D), and sleep quality by the Pittsburgh sleep quality index (PSQI) were recorded. RESULTS: Twenty-two out of 382 patients [64% women; age, 24.7 years (4–68)] examined during the pandemic (6 months) had FMDs compared to 31/1462 [67% women; age, 26.9 years (5–63)] examined in the pre-pandemic period, showing a 2.71-time increase. Among FMDs, functional myoclonus was the most common (36.4%), followed by functional gait disorder (27.2%), functional tremor (18.2%), functional dystonia (9.1%), and mixed phenotype (9.1%). Furthermore, 90.9% had an abnormal score (>11) on HADS-A or HADS-D and 86.3% had a score of >5 on PSQI, indicating poor sleep quality. There was a strong correlation between higher anxiety scores (P < 0.001) and poor sleep quality (P < 0.005) with an increase in frequency of FMD during the pandemic. CONCLUSION: The frequency of FMDs was 2.71 times higher during the pandemic, suggesting the vulnerability of predisposed patients (as evidenced by their elevated HADS scores) during stressors. Coexistent anxiety and depression increase the risk of FMDs, of which functional myoclonus was the most common phenotype, followed by gait disorders and functional tremor. Recognizing this entity will help avoid unnecessary work-up, which can be economically draining in such trying times.